2022
DOI: 10.1111/exsy.13179
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of China's regional innovation capability based on simulated annealing projection pursuit model and nested fuzzy evaluation model

Abstract: Regional innovation capability is an important indicator of both regional innovative and long‐term development. The purpose of this study is to build an evaluation index system for regional innovation capability in order to identify regional differences and support innovation more effectively. After establishing a reasonable evaluation value for regional innovation capability, a combination of simulated annealing optimized projection pursuit (SA–PP) and N‐layer nested fuzzy comprehensive evaluation models is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Song [16] proposed a hierarchical hybrid genetic algorithm, backpropagation neural network, and the PPM for the comprehensive evaluation of groundwater quality. Ge and Lin [17] used the PPM optimized by a genetic simulated annealing (GSA) algorithm to analyze the complex correlations among indices of an evaluation model for regional innovation capacity in China. These studies demonstrated the PPM's high stability and reliability in multi-attribute comprehensive evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…Song [16] proposed a hierarchical hybrid genetic algorithm, backpropagation neural network, and the PPM for the comprehensive evaluation of groundwater quality. Ge and Lin [17] used the PPM optimized by a genetic simulated annealing (GSA) algorithm to analyze the complex correlations among indices of an evaluation model for regional innovation capacity in China. These studies demonstrated the PPM's high stability and reliability in multi-attribute comprehensive evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…Ge and Lin (2023) make an evaluation of China's regional innovation capability based on a simulated annealing projection pursuit model and nested fuzzy evaluation model. The authors intend to establish an evaluation index system for regional innovation capacities to better understand regional variances and promote innovation.…”
mentioning
confidence: 99%